2019
DOI: 10.1097/prs.0000000000006102
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Statistically Significant Randomized Controlled Trials in Plastic Surgery

Abstract: Background: The fragility index has been proposed as a metric to evaluate the robustness of statistically significant findings in randomized controlled trials. It measures the number of events that a trial result relies on to maintain statistical significance. This study examines the robustness of statistically significant results from randomized controlled trials in the plastic surgery literature. Methods: A systematic literature search of the 15 highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The median FI was 2 (IQR: 0–4). Eleven studies reported higher FI values associated with lower p values for significant outcomes ( p < = 0.05) [2, 14, 15, 21, 23, 26, 32, 34, 35, 50, 51]. One study reported no correlation between FI and p values for significant outcomes [22].…”
Section: Resultsmentioning
confidence: 99%
“…The median FI was 2 (IQR: 0–4). Eleven studies reported higher FI values associated with lower p values for significant outcomes ( p < = 0.05) [2, 14, 15, 21, 23, 26, 32, 34, 35, 50, 51]. One study reported no correlation between FI and p values for significant outcomes [22].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, any synthesis of related RCTs, although it may present low heterogeneity, carries an inherited risk of extrapolated findings. To nutrition's defence however, lower median FI compared with that of MD interventions has been reported in perioperative, 81 anesthesiology, 82 plastic surgery, 83 and critical-care medicine 84 RCTs, as well as among paediatric orthopedic 85 and appendicitis 86 trials. Nevertheless, the synthesis of these trials for recommendations formulation consists of a common practice in the fields mentioned above, as in the science of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This is a consideration that holds true in other fields of medicine, and a systematic survey of plastic surgery RCTs found that 27% had an FI of 0. 40…”
Section: Discussionmentioning
confidence: 99%
“…3 By comparison, an analysis of the 15 highest impact plastic surgery journals found that a median of one event change led to a loss of statistical significance. 40 In ophthalmology, the median FI was 2, with a median sample size of 92.…”
Section: Discussionmentioning
confidence: 99%